Respostas
respondido por:
2
y = x² - 2x - 3
Ponto de interseção com o eixo das ordenadas: x = 0
Então, y = 0² - 2.0 - 3
y = -3
Ponto de interseção P'=(0,-3)
Ponto de interseção com o eixo das abscissas: y = 0
Então, 0 = x² - 2x - 3
x = (2 + √(-2²)-4.1.(-3))/2
x = (2 + √16)/2
x = (2+4)/2
x = 3
Ponto de interseção P''=(3,0)
Ponto de interseção com o eixo das ordenadas: x = 0
Então, y = 0² - 2.0 - 3
y = -3
Ponto de interseção P'=(0,-3)
Ponto de interseção com o eixo das abscissas: y = 0
Então, 0 = x² - 2x - 3
x = (2 + √(-2²)-4.1.(-3))/2
x = (2 + √16)/2
x = (2+4)/2
x = 3
Ponto de interseção P''=(3,0)
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás